Phenolic-Rich Annona muricata L. Leaf Extract Provides Broad-Spectrum Photoprotection: Linking SPF Enhancement with UVB/UVA Transmission Reduction (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
The search for safer, more environmentally friendly ultraviolet (UV) filters has led to the exploration of bioactive plant compounds as alternatives to synthetic UV filters. This study evaluates the phytochemical composition and photoprotective potential of ethanol extracts from Annona muricata L. leaves as candidates for a natural photoprotective ingredient. The ethanol extract of soursop leaves contains polyphenolic secondary metabolites with a total phenolic content of 67.30 ± 1.27 mg GAE/g extract and a total flavonoid content of 63.62 ± 0.67 mg QE/g extract. These phenolic and flavonoid compounds contribute to photoprotective activity. With increasing extract concentrations, the SPF value rose significantly (p
Keywords: Annona muricata leaf extract; UVB/UVA transmission; Natural photoprotection; Sun protection factor (SPF); Transmission phenolic